Wind speed in spring dominated the decrease in wind erosion across the Horqin Sandy Land in northern China. (August 2021) - Zhang, Hanbing; Peng, Jian; Zhao, Chaonan; Xu, Zihan; Dong, Jianquan; Gao, Yang
Abstract: Wind erosion is the main cause of land degradation and desertification in drylands. Severe wind erosion affects regional ecological security and endangers the health of people. The Horqin Sandy Land is one of the largest sandy lands in China. It suffers from severe wind erosion and is one of the main sources of sand storms in the Beijing–Tianjin–Hebei region. The spatiotemporal dynamics of wind erosion and its driving factors were explored in this study by using the Revised Wind Erosion Equation to evaluate wind erosion in the Horqin Sandy Land from 2001 to 2016. The year was divided into four phases according to the distribution of the wind erosion modulus, and the differences between the annual scale and the seasonal scale wind erosion characteristics were analyzed. The annual average wind erosion across the Horqin Sandy Land from 2001 to 2016 was 5.50 t/hm 2, and wind erosion showed an obvious downward trend at a speed of 0.82 t/hm 2 /a. High intensity wind erosion mainly occured from March to May, which accounted for 67.95% of the total erosion per year. Although the wind erosion in each phase of the year showed downward trends, the rate in the spring was substantially higher than that in other phases. The main reasons for the decrease in wind erosion were the reduction in wind speed and the restoration of vegetation, with the contribution of −55.78% and −42.68%, respectively. Vegetation coverage dominated the decline in wind erosion in a number of areas, but areas with severe wind erosion were dominated by wind speed. Furthermore, wind speed in the spring was the dominant factor driving the decline in wind erosion across the Horqin Sandy Land. Major wind erosion control programs should be aimed to restore vegetation in severely desertified areas of the Horqin Sandy Land.